Lesion revascularisation subsequent to femoropopliteal spot stenting using the multi-LOC stent delivery system - Sigl, Martin; Amendt, Klaus; Waliszewski, Matthias; Rathmann, Nils-Andreas (In vivo, 2020)
Background/Aim: Restenosis and stent fractures are well-characterised treatment failures following femoropopliteal (FP) stent-based interventions. We aimed to determine patterns of restenosis and fracture rates following focal stenting of FP arteries. Patients and Methods: This retrospective study investigated angiographic patterns of restenosis and the occurrence of stent fractures following focal FP stenting with the multiple stent delivery system VascuFlex® Multi-LOC. Results: We identified 10 patients with 10 (of 129) FP lesions (mean length 11.7±4.6 cm) and a total of 51 (of 646) Multi-LOC stents that underwent clinically driven target lesion revascularizations (TLR) after 11.5±9.2 months, due to symptomatic recurrence of stenosis. None of the Multi-LOC stents had fractured. No isolated in-stent restenosis (>50%) was observed. Median diameter lumen loss was significantly more pronounced at the inter-stent segments (27.0%) compared to in-stent segments (7.8%, p=0.023). Conclusion: No evidence of fracture or susceptibility to stent-related restenosis using Multi-LOC stents was observed. Focal FP stenting may be more effective when combined with strategies known to reduce restenosis in non-stented artery segments.
Gesehen am 10.03.2020